2006
DOI: 10.1186/1471-2458-6-238
|View full text |Cite
|
Sign up to set email alerts
|

A knowledge, attitudes, and practice survey among obstetrician-gynaecologists on intimate partner violence in Flanders, Belgium

Abstract: Background: Intimate partner violence (IPV) has consistently been found to afflict one in twenty pregnant women and is therefore considered a leading cause of physical injury, mental illness and adverse pregnancy outcome. A general antenatal screening policy has been advocated, though compliance with such guidelines tends to be low. We therefore attempted to identify potential barriers to IPV screening in a context where no guidelines have been instigated yet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
90
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 38 publications
11
90
0
1
Order By: Relevance
“…It is likely that training in this area will help providers recognize signs and symptoms of IPV, direct their inquiries appropriately and efficiently, and allow them to provide appropriate advice and treatment to victims. Physician training in the recognition and management of female patients with IPV was associated with greater preparedness on the part of providers for screening and assistance of such patients [17,24]. Only approximately 1 .…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that training in this area will help providers recognize signs and symptoms of IPV, direct their inquiries appropriately and efficiently, and allow them to provide appropriate advice and treatment to victims. Physician training in the recognition and management of female patients with IPV was associated with greater preparedness on the part of providers for screening and assistance of such patients [17,24]. Only approximately 1 .…”
Section: Discussionmentioning
confidence: 99%
“…However, research suggests that most violence victims do not report their experiences without being asked (Roelens et al 2006) and, as noted above, midwives indicated that they recognised that violence could be concealed. Midwives also recognised that one needed a great deal of time and skill to identify a case.…”
Section: Identifying Abused Women: Current Practicementioning
confidence: 99%
“…Although routine screening for violence in health settings has been endorsed by many health professional organisations, including the US academies and colleges of gynaecologists and paediatricians (Roelens et al 2006;Waalen et al 2000), few health settings in the world have begun implementing this intervention. Most African health settings do not meet the above criteria for comprehensive programmes to respond to IPV because of their weak health systems, lack of infrastructure and human resources as well as cultural reasons that inhibit discussing or disclosing domestic life outside of the home.…”
Section: Introductionmentioning
confidence: 99%
“…31 This study's finding that gynaecologists and/or obstetricians irrespective of their sex were least willing to help and more inclined to blame the survivors, is not consistent with Roelens and colleagues' study where the majority of gynaecologists and/or obstetricians disagreed with the question 'Do you agree that women may harass their spouses so badly/to the extent that is conceivable for husbands to lose their temper?'. 32 This surprising finding, although based on interviews with a small sample of physicians need to be further elucidated.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%